The Efficacy and Safety of the Combined Therapy of Sodium-Glucose Co-Transporter-2 Inhibitors and Angiotensin Receptor-Neprilysin Inhibitor in Patients With Heart Failure With Reduced Ejection Fraction: A Meta-Analysis of the EMPEROR-Reduced and DAPA-HF Sub-Analysis - Lin, Yanxia; Zhang, Huanrui; Zhao, Shijie; Chen, Ling; Li, Jinyang; Wang, Xiaoou; Tian, Wen (Frontiers in Cardiovascular Medicine, 2022)
Background: Both sodium-glucose co-transporter-2 (SGLT-2) inhibitors and angiotensin receptor-neprilysin inhibitor (ARNI) were recommended to treat heart failure with reduced ejection fraction (HFrEF). However, no trial was powered to assess the efficacy and safety of the combined therapy of SGLT-2 inhibitors and ARNI in patients with HFrEF. Methods: We performed a meta-analysis of the prespecified subgroups from DAPA-HF and EMPEROR-Reduced trials. The primary endpoint was the composite risk of cardiovascular death or hospitalisation for heart failure. The risk of cardiovascular death, all-cause death, composite of serious adverse renal outcomes, and volume depletion were also estimated. Results: The risk of composite of cardiovascular death or hospitalisation for heart failure was reduced in combined therapy of SGLT2 inhibitors and ARNI, compared with ARNI monotherapy (RR 0.68, 95% CI 0.53 to 0.85, P = 0.001). When compared with SGLT-2 inhibitors monotherapy, the events of cardiovascular death (RR 0.64, 95% CI 0.46 to 0.87, P = 0.005) and all-cause death (RR 0.72, 95% CI 0.55 to 0.94, P = 0.01) were significantly less in combined therapy, accompanied by elevated incidence of volume depletion (RR 1.55, 95% CI 1.22 to 1.96, P = 0.0003). Conclusions: Combined therapy has additional benefits over monotherapy in patients with HFrEF, however, accompanied by possibly higher risk of volume depletion.